ANALISA FINANSIAL PADA USAHA PERSEMAIAN BIBIT ULIN OLEH MASYARAKAT DI DESA SUNGAI MERDEKA KECAMATAN SAMBOJA - Idrus ,Abdul Kholik Hidayah, dan Ismail Bakrie (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
This study aimed to determine: (1) Business profit of ironwood seedlings nursery (Eusidroxy zwageri T, et B) in the village of Sungai Merdeka. (2) Eligibility of ironwood seedling nursery business in the village of Sungai Merdeka.The study population was all ironwood seedler/farmers in villages of Sungai Merdeka, Samboja sub district, which total 15 people.  Data collection using observation, interview and note taking. Instrument of data collection using questionnaires.Result of the descriptive analysis revealed that the average revenue of ironwood seedling nursery of 0.10 ha  giving Rp 143,000,000.00, income of Rp 92,523,701.67, and a profit Rp 92,057,535.00.  Result of the analysis showed that ironwood seedling nursery businesses is feasible, as it can be seen from the R/C ratio is 2.81;  Production > BEP production volume (28,600 > 1.521) and the selling price > of BEP Price (5.000 > 1.781)